Autoimmune pulmonary alveolar proteinosis with a history of vaping and vitamin E‐positive bronchoalveolar lavage. Issue 11 (18th October 2021) - Chua, Tzy Harn; Takano, Angela; Yao, Yi Ju; Chow, Sau Yee; Devanand, Anantham; Tay, Chee Kiang
Abstract: Pulmonary alveolar proteinosis (PAP) can be due to primary autoimmune and secondary causes, including e‐cigarette, or vaping, product use‐associated lung injury. We present a 33‐year‐old male presenting with PAP and a history of vaping. Serum anti‐granulocyte‐macrophage colony‐stimulating factor antibodies were present. Vitamin E (VE), but not VE acetate, was detected in bronchoalveolar lavage. This is the first report of potential association between vaping and autoimmune PAP. Abstract : We present a 33‐year‐old male presenting with pulmonary alveolar proteinosis (PAP) and a history of vaping. Serum anti‐granulocyte‐macrophage colony‐stimulating factor antibodies were present. Vitamin E (VE), but not VE acetate, was detected in bronchoalveolar lavage. This is the first report of potential association between vaping and autoimmune PAP.